2004
DOI: 10.1007/s00167-004-0506-8
|View full text |Cite
|
Sign up to set email alerts
|

Tendon regeneration: an anatomical and histological study in sheep

Abstract: Utilization of the hamstring tendon in reconstruction of the anterior cruciate ligament (ACL) has become common in recent years. In MRI studies regeneration potential in harvested tendon has been observed. In the present study, 20 legs from ten sheep, which underwent 10 cm segment resection of tendon of musculus extensor digitalis lateralis (MEDL) were used. The sheep were killed 6 months after the operation and regenerated tendons were examined macroscopically and histologically. Dissection was performed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…The study revealed that equal tension in the regenerated ST tendons and adjacent G tendons, when performing a voluntarily hamstring contraction, indicated a functional muscle tendon complex with good mechanical properties. The result rate of 72 % of the ST tendon regeneration revealed regenerated tendon tissue with a normal histological appearance, similar to the control tendon, and the knee evaluation form results showed minimal hamstring strength deficit of the harvested tendon, in agreement with previous studies [7,15,16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study revealed that equal tension in the regenerated ST tendons and adjacent G tendons, when performing a voluntarily hamstring contraction, indicated a functional muscle tendon complex with good mechanical properties. The result rate of 72 % of the ST tendon regeneration revealed regenerated tendon tissue with a normal histological appearance, similar to the control tendon, and the knee evaluation form results showed minimal hamstring strength deficit of the harvested tendon, in agreement with previous studies [7,15,16].…”
Section: Discussionsupporting
confidence: 89%
“…Both in vitro and in vivo studies have illustrated "intrinsic" and "extrinsic" healing potential of the injured or surgically reconstructed tendon, although some have shown a regenerative process of the full-length tendon [13][14][15]. One research investigated the arterial supply of the pes anserinus tendons at the tibial attachment, but not the whole length of the tendons [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the studies of Papandrea et al [13] and especially of Rispoli et al [15] confirmed the previous findings. Nevertheless, in a recent study of sheeps, Turhan et al [25] have found that the harvested tendons of musculus extensor digitalis lateralis regenerated in all cases but the regeneration occurred proximally and distally at the same time, thus raising questions about the direction of the regeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the mature collagen fiber has a typical periodic banding pattern (64–70 nm) (Doherty, 2007). Thus, a tendon is recognizable by the organization of its fibers: regularly arranged, wavy appearing collagen bundles and fibrocyte nuclei (Turhan et al, 2004). According to our data, this organization is reached only in juvenile specimens of L. latinasus.…”
Section: Discussionmentioning
confidence: 99%